Aging and Comorbidities in Acute Pancreatitis I: A Meta-Analysis and Systematic Review Based on 194,702 Patients - Márta, Katalin; Lazarescu, Alina-Marilena; Farkas, Nelli; Mátrai, Péter; Cazacu, Irina; Ottóffy, Máté; Habon, Tamás; Erőss, Bálint; Vincze, Àron; Veres, Gábor; Czakó, László; Sarlós, Patrícia; et al. (Frontiers in Physiology, 2019)
Acute pancreatitis (AP) is one of the most common cause of hospitalization among gastrointestinal diseases worldwide. Although most of the cases are mild, approximately 10%-20% of patients develop a severe course of disease with higher mortality rate. Scoring systems consider age as a risk factor of mortality and severity (BISAP;>60yrs, JPN>70 yrs, RANSON;>55yrs, APACHE II>45 yrs). If there is a correlation between ageing and the clinical features of AP, how does age influence mortality and severity? This study aimed to systematically review the effects of aging on AP. A comprehensive systematic literature search was conducted in the Embase, Cochrane and Pubmed databases. A meta-analysis was performed using the preferred reporting items for systematic review and meta-analysis statement (PRISMA). A total of 1100 articles were found. After removing duplicates and articles containing insufficient or irrelevant data, 33 publications involving 194 702 AP patients were analyzed.Seven age categories were determined and several mathematical models, including conventional mathematical methods (linear regression), meta-analyses (random effect model and heterogeneity tests), meta-regression, funnel plot and Egger’s test for publication bias were performed. Quality assessment was conducted using the modified Newcastle–Ottawa scale.The meta-analysis was registered in the PROSPERO database (CRD42017079253). Aging greatly influences the outcome of AP. There was a low severe AP incidence in patients under 30(1.6%); however, the incidence of severe AP showed a continuous, linear increase between 20 and 70(0.193%/year) of up to 9.6%. The mortality rate was 0.9% in patients under 20 and demonstrated a continuous linear elevation until 59,however from this age the mortality rate started elevating with 9 times higher rate until the age of 70.The mortality rate between 20 and 59 grew 0.086%/year and 0.765%/year between 59 and 70. Overall, patients above 70 had a 19 times higher mortality rate than patients under 20. The mortality rate rising with age was confirmed by meta-regression (coefficient:0.037CI:0.006–0.068,p=0.022;adjustedr2:13.8%),and severity also (coefficient:0.035CI:0.019–0.052,p<0.001;adjusted r2:31.6%). Our analysis shows a likelihood of severe pancreatitis, as well as, pancreatitis-associated mortality is more common with advanced age. Importantly,the rapid elevation of mortality above the age of 59 suggests the involvement of additional deteriorating factors such as co-morbidity in elderly.